Students’ Listening Skill Using Cognitive Summarizing Strategies - Indri Puspita Sari; Tera Athena; Moh. Kurdi Wijaya (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2023)
This study aims to know the implementation of cognitive summarizing strategies in teaching learning listening class, the researcher was chosen cognitive summarizing as strategy to deliver the material to the students. This study was descriptive qualitative research and conducted on June 17th – 18th, 2020. The participants of this research were the English teacher and the students of XI MIPA 2 at SMA Negeri 1 Arosbaya. The data were obtained by observing the students, the teacher, and the implementation of cognitive summarizing strategies listening class by making a transcript and screenshot of the result. The result of the observation indicates that the implementation of cognitive summarizing strategies in listening class makes the students more enthusiastic about the material and they can deliver what they have been heard from the podcasts or audio using their own words.